Formulation of the Problem of Maximum Clique Determination in Non-Oriented Graphs - V. Listrovoy, S.; V. Golovko, O.; M. Butenko, V.; V. Ushakov, M.; ., . (International Journal of Engineering and Technology, 2018)
In the train traffic organization, large amount of information should be processed in real time. Thereby in complicated dispatching systems, rational use of resources is needed. To perform this work a model of a management system is constructed and it is represented as a sparse graph. Further optimization of the model requires solving the Maximum Clique Problem (MCP) for the less time than the exponential time. This article contains two procedures for solving the task for subexponential time. Procedure B accurately estimates the size of the maximum clique in the graph and performs the sorting of the vertices, in such a way that the vertices that are not exactly in the maximum clique can be rejected. Procedure A, in fact, finds cliques of the maximum size in a given graph, using the procedure B. The main advantage of this method is that using it is expedient in real time for sufficiently large graphs, which in turn is important for the construction of control systems.Â Â
Keywords: cliques in non-oriented graph; cost optimization tools; maximum clique problem; railway infrastructure; safety of control systems